Using of Tax Incentives in Activating the Accounting for Environmental Impacts in the Sudanese Industrial Companies: Accounting Vision in the Light of Sudanese Income Tax Act of 1986 - Mohammed, Fatihelelah (The Arab Journal of Administration, 2021)
The study aimed to clarifying the legal areas in the Income Tax Act of Sudan of 1986, which could encourage relevant companies on the activation of accounting for the environmental impacts in their financial reports, then to identify management’s perspective on the extent of the impact of tax incentives for encouraging the activation of accounting for environmental impacts. To achieve these objectives, the Income Tax Act of Sudan for the year 1986 has been reviewed, together with identification of areas that can represent tax incentives for industrial companies to activate accounting for environmental impacts. A questionnaire has been prepared and distributed to (165) participants from higher managements. The main findings of the study have come to the following: Impact of the deduction of the expenses of environmental pollution in activating the accounting for environmental impacts differs from the industrial sector to another according to the nature of the Activity. Discounts, reductions and exceptions in the tax burden encourage the industrial companies in term of activation of accounting for the environmental impacts in their financial reports. The study recommended that the Sudanese tax legislature must develop tax legislation and expanded to include the environmental dimension and restructure incentives in the income tax act of 1986 to include accounting for environmental dimensions.